1997
DOI: 10.1001/archneur.1997.00550200046009
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functions in Major Depression and Parkinson Disease

Abstract: Major depression in patients with PD is associated with significant deficits on specific cognitive tasks. While some of these deficits may be explained by the presence of major depression, frontal lobe-related cognitive impairments may result from an interaction between neuropathologic factors in PD and the mechanism of major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2
7

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(82 citation statements)
references
References 18 publications
5
68
2
7
Order By: Relevance
“…To generate words in these tasks, subject must plan and initiate a systematic search of memory (15). Performance in letter fluency test is reported both as intact (16) and impaired in PD patients (17). Compared to controls, our PD patients showed significantly inferior performance in this task.…”
Section: Discussionmentioning
confidence: 99%
“…To generate words in these tasks, subject must plan and initiate a systematic search of memory (15). Performance in letter fluency test is reported both as intact (16) and impaired in PD patients (17). Compared to controls, our PD patients showed significantly inferior performance in this task.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an association between depression and cognitive impairments in PD patients [22][23][24][25][26][27][28][29][30]. There are, however, a few other studies that did not detect a significant association between depression and variance in cognitive deficit in PD (See table 1) [31][32][33][34].…”
Section: Depressionmentioning
confidence: 99%
“…In terms of executive dysfunction, several studies have reported that patients with depression performed significantly lower than non-depressed patients on tests of executive function including the Wisconsin Card Sort Test (WCST) [35], Controlled Word Association Test-FAS [36], Trail Making Test (TMT) (A and B) [37], Verbal Fluency, Abstract Reasoning, Design Fluency Test (Free condition) [38] and the Symbol Digit Modalities [39], [25,28,30] . Other studies have also demonstrated that depressed PD patients had lower scores relative to non-depressed PD patients using a variety of executive tasks e.g.…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties with memory, attention, and language are also common in PD and are frequently aggravated by depression [8,59,60,61,62]. This widespread cognitive impairment has been noted despite the absence of clinically significant cognitive decline [8].…”
Section: Expert Commentary Unique Features Of Dpdmentioning
confidence: 99%